Do permit allocations matter? - Harrie A. A. Verbon; Cees A. Withagen (Center for Economic Studies and ifo Institute (CESifo), 2010)
In the standard setting a system of tradable permits is effective and cost-efficient in attaining the policy objective of pollution reduction. This outcome is challenged in case of a tradable permit system in a federal system/constitution with individual states having discretionary power regarding environmental policy and where pollution is transboundary across states. This paper explores the opportunities of the central authority to influence the effectiveness and efficiency of the system, under various institutional arrangements, through the initial allocation of permits.
Keywords: H21; H23; Q00; 330; tradable permits; fiscal federalism; Emissionsrechte; Emissionshandel; Finanzföderalismus; Umweltpolitik; Allokation